Using Photography to Visualize Children's Culture of Play: A Socio‐Spatial Perspective. Issue 1 (January 2014) - Wee, Bryan Shao‐Chang; Anthamatten, Peter
Abstract Visual methodologies have great potential to offer insight into children's culture and how it shapes childhood. We explore children's culture of play in an urban, low‐income neighborhood using photographs as a means of encouraging participatory research with elementary school students. Focus group interviews were conducted to validate children's perspectives on play, and all data were analyzed inductively using open coding to develop categories and emergent themes. Findings suggest that adults often define the physical boundaries of play, but children were largely able to determine the nature of their activities. Children's culture of play in this study highlighted issues of power and privilege, while concurrently emphasizing the socio‐spatial nature of childhood.